A model to evaluate effectiveness of lean and ISO 14001 implementation on environmental benefits in the meat industry : a thesis presented in partial fulfillment of the requirement for the degree of Doctor of Philosophy in Engineering Management, School of Food and Advanced Technology, Massey University, Auckland, New Zealand - Ahmed, Aqeel (Massey University, 2024)
Excessive emissions of greenhouse gases, production of wastes (organic and inorganic) and inefficient utilisation of resources have drastic impacts on the operational and environmental performance in the meat industry. Reducing waste and processing environmentally friendly meat products have long been desired in meat processing and is still considered as a promising strategy to yield environmentally friendly products. ISO 14001 is a voluntary environmental management system standard that provides a continuous improvement framework to reduce environmental impacts and improve environmental performance. Lean is used as a strategy for minimising waste and non-value-adding activities focusing on increasing customer satisfaction, which also has a positive impact on the environment. Besides, continuous improvement is at the very core in both approaches. This study evaluates the environmental performance in the meat industry through the joint application of lean and ISO 14001. Further, a conceptual model is developed through literature synthesis which combines the lean and ISO 14001 strategies to achieve the environmental performance benefits that could be applied to the meat industry. The study uses the natural resource-based view (NRBV) as its theoretical lens to understand lean and ISO 14001 implementation as a combined approach for improving environmental performance outcomes in the meat industry. A preliminary study and subsequent multiple-case studies are employed as a qualitative research design for this evaluation. In the first phase of the study, semi-structured interviews with lean and ISO 14001 consultants are conducted to evaluate the implementation of lean and ISO 14001 as a combined approach for improving environmental performance in the meat industry. Next, multiple-case studies are conducted in three meat processing organisations – two in New Zealand and one in Ireland – to evaluate the effectiveness of implementing both lean and ISO 14001 strategies together for achieving environmental benefits. This study reveals that the application of the NRBV competencies (e.g., strategic planning and human) for a joint lean and ISO 14001 implementation helps to enhance natural capabilities (i.e., pollution prevention, product stewardship and sustainable development). For instance, lean and ISO 14001 implementation as a combined approach helps to better achieve pollution prevention (e.g., reduction of wastewater and greenhouse gas emissions), product stewardship (e.g., recycling of wastewater and introduction of renewable resources) and sustainable development (e.g., sustainable resources usage and environmental awareness). This research contributes to presenting key practitioner insights on the implementation of lean and ISO 14001 for improvement of environmental performance as well as provides factors for successful implementation of both strategies in the meat industry. A model is developed for lean and ISO 14001 implementation through empirical evidence and competencies and capabilities of the NRBV lens to help practitioners, policymakers, consultants and academia in their future work to improve environmental performance.
Figure 2.2 is reproduced under a Creative Commons Attribution-Non Commercial 3.0 license.
Keywords: lean, ISO 14001, environmental performance, meat industry; 401106 Waste management, reduction, reuse and recycling